2020
DOI: 10.7185/geochemlet.2008
|View full text |Cite
|
Sign up to set email alerts
|

Massive sulfide Zn deposits in the Proterozoic did not require euxinia

Abstract: Our most important Zn resources occur within clastic-dominated (CD-type) deposits, which are located in a small number of Proterozoic and Phanerozoic sedimentary basins. The most common model for CD-type mineralisation involves sedimentary exhalative (SEDEX) processes, i.e. the venting of metal bearing fluids into a restricted, anoxic H 2 S-bearing (euxinic) water column. In the Carpentaria Zn Province (Australia), multiple world class deposits are hosted in Proterozoic (1.6 Ga) stratigraphy, where models of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…There are multiple marine transgressions that can be mapped across subbasins by the preservation of pyritic and carbonaceous facies that represent maximum flooding surfaces (MFS). Two MFS have been identified in the Teena subbasin (Magnall et al, 2020), which can be correlated across other subbasins in regional studies of the Barney Creek Formation in the southern McArthur Basin (Kunzmann et al, 2019).…”
Section: Stratigraphymentioning
confidence: 78%
See 2 more Smart Citations
“…There are multiple marine transgressions that can be mapped across subbasins by the preservation of pyritic and carbonaceous facies that represent maximum flooding surfaces (MFS). Two MFS have been identified in the Teena subbasin (Magnall et al, 2020), which can be correlated across other subbasins in regional studies of the Barney Creek Formation in the southern McArthur Basin (Kunzmann et al, 2019).…”
Section: Stratigraphymentioning
confidence: 78%
“…The stratiform mineralization is located >150 m (current thickness) below the MFS in the Middle HYC unit, which contains particularly high abundances of carbonaceous material and pyrite (Fig. 3B; Magnall et al, 2020). It has been suggested elsewhere that the most reducing facies (e.g., the MFS) should be targeted in SEDEX exploration models (e.g., Emsbo, 2009).…”
Section: Controls On Mineralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…8I). Further study of the chemistry of these different pyrite generations will be necessary to assess if the chemical and isotopic composition of the diagenetic pyrite can be distinguished from the hydrothermal pyrite, as has been shown in other deposits (Large et al, 2009;Gadd et al, 2016;Magnall et al, 2020c).…”
Section: Implications For the Genesis Of And Exploration For CD Depositsmentioning
confidence: 99%
“…Contrary to the SEDEX model, many researchers have made petrographic arguments that CD-type deposits formed via replacement processes during diagenesis (Grondijs and Schouten, 1937;Williams, 1978;Magnall et al, 2020a;Spinks et al, 2021). Furthermore, recent studies have shown that the protolith of CD-type deposits accumulated under a range of depositional redox conditions, albeit with minimal evidence of prolonged euxinia (Reynolds et al, 2015;Magnall et al, 2018Magnall et al, , 2020b.…”
Section: Introductionmentioning
confidence: 99%